2016
DOI: 10.1155/2016/7981397
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of α‐Mangostin on the Cytotoxicity of Cisplatin in a Cervical Cancer Model

Abstract: Cervical cancer is the second leading cause of death among Mexican women. The treatment with cis-diamminedichloroplatinum (II) (CDDP) has some serious side effects. Alpha-mangostin (α-M), has a protective effect against CDDP-induced nephrotoxicity, as well as antioxidant, antitumor, and anti-inflammatory properties. Hence, we explored the in vitro and in vivo effect of α-M on human cervical cancer cell proliferation when combined with CDDP. In vitro, The cytotoxic effect of α-M and/or CDDP was measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
(61 reference statements)
2
26
0
Order By: Relevance
“…Our previous study demonstrates that α‐mangostin can activate reactive oxygen species signaling and induce apoptosis of HeLa cell (Lee et al, 2017), suggesting that α‐mangostin has potential anticancer activity against cervical cancer cells. Similarly, α‐mangostin has been reported to show a synergistic effect on cisplatin‐induced cytotoxicity on the HeLa cell in vitro and in vivo (Perez‐Rojas et al, 2016). In addition, α‐mangostin also has a protective effect on cisplatin‐induced kidney injury (Perez‐Rojas et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study demonstrates that α‐mangostin can activate reactive oxygen species signaling and induce apoptosis of HeLa cell (Lee et al, 2017), suggesting that α‐mangostin has potential anticancer activity against cervical cancer cells. Similarly, α‐mangostin has been reported to show a synergistic effect on cisplatin‐induced cytotoxicity on the HeLa cell in vitro and in vivo (Perez‐Rojas et al, 2016). In addition, α‐mangostin also has a protective effect on cisplatin‐induced kidney injury (Perez‐Rojas et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Cell viability was estimated by MTT ((3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide)) assay as described previously. 37 …”
Section: Methodsmentioning
confidence: 99%
“…The structural diversity and biological aspects of xanthones make these secondary metabolites attractive to researchers, in the search for new and potent anticancer drug candidates . In recent years, studies on the anticancer and anti‐inflammatory activities of xanthones have shown significant results, mostly demonstrating their efficacy and low toxicity in normal cells …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…[194] In recent years, studies on the anticancer and anti-inflammatory activities of xanthones have shown significant results, mostly demonstrating their efficacy and low toxicity in normal cells. [195,196] Table 2. Overview of the main synthetic routes to obtain xanthone derivatives.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%